The changes in Blood Pressure in Patients Undergoing Spinal Anesthesia According to the Size of Spinal Needle (G22 versus G24): Case Reference Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Previous studies of patients with spinal anesthesia prior to sympathectomy revealed thatvasodilatation and hypotension, with subsequent reduction in arterial pressure, were the most common sideeffects (observed in more than 30% of patients). Hypotension in epidural anesthesia was stated to be moregradual and less extreme than in spinal anesthesia when a comparable amount of anesthesia was given.Aim of the study: In the current study, we are aiming to evaluate the effect of different size of spinal needleon development of possible blood pressure changes throughout the spinal anesthesia procedure.Patients and Methods: The current observational case reference study was carried out at Al-DiwaniyahTeaching Hospital in Al-Diwaniyah Province, Iraq. The beginning of the study is dated back to the 3rd ofApril 2018 and the study continued till September the 15th 2019. It included 60 patients undergoing spinalanesthesia for various surgical operations. In 30 patients a spinal needle of 22 gauge was used whereas inthe second group (n = 30), a spinal needle of gauge 24 was used. All patients were instructed to be nil bymouth overnight.Results: In group 1 (22G), mean systolic blood pressure showed gradual reduction, 139.00 ±8.35 mmHG,120.67 ±11.43 mmHg, 106.00 ±11.02 mmHG and 97.33 ±10.15 mmHg; similarly, in group 2 (24G) meansystolic blood pressure showed gradual reduction, 144.00 ±10.37 mmHG, 138.00 ± 7.61 mmHg, 131.33±9.00 mmHG and 131.67 ±11.40 mmHg; however, the rate of reduction in group 2 (G24) was less than thatseen in case of group 1 (G22). In group 1 (22G), mean diastolic blood pressure showed gradual reduction,84.00 ±7.24 mmHG, 72.00 ±6.64 mmHg, 61.33 ±9.73 mmHG and 54.00 ±8.94 mmHg; similarly, in group2 (24G) mean diastolic blood pressure showed gradual reduction, 87.33 ±7.85 mmHG, 81.33 ±7.30 mmHg,77.33 ±10.15 mmHG and 78.00 ±5.51 mmHg; however, the rate of reduction in group 2 (G24) was less thanthat seen in case of group 1 (G22).Conclusion: It appears that the use of narrower spinal needle is recommended as it is associated withsignificantly less drop in both systolic and diastolic blood pressure, thus less hemodynamic disturbances inpatients undergoing spinal anesthesia for various indications
Keywords: blood pressure, spinal anesthesia according, spinal needle (G22 versus G24)